2005
DOI: 10.1063/1.2048568
|View full text |Cite
|
Sign up to set email alerts
|

Continuation calculations of boron- (aluminum-, titanium-, and nickel-) doped La13 clusters

Abstract: In this work, we have calculated boron-, aluminum-, titanium-, and nickel-doped La13 clusters by DMOL method based on the density-functional theory. Two doping modes are employed: surface and center doping. The boron, aluminum, and nickel atoms prefer to occupy the surface sites while the titanium atom prefers to occupy the center site. The doped La13 clusters with these four kinds of atoms have lower binding energy than pure La13 clusters. The icosahedral isomers are of lower binding energy than cubotahedral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The different gap between the spin‐up and spin‐down electrons of the Ni n B clusters indicate that it could be used as a spin‐polarized transport system 12. It was found that the total magnetic moments (TMM) quench in the charged AlLa 12 and BLa 12 clusters with the icosahedral structure 13. Nigam et al studied that the 3 d TM atoms doped the Pd 12 clusters and found that the magnetic characteristics of the Pd 13 clusters were significantly influenced by the dopant 3 d TM atoms 14.…”
Section: Introductionmentioning
confidence: 99%
“…The different gap between the spin‐up and spin‐down electrons of the Ni n B clusters indicate that it could be used as a spin‐polarized transport system 12. It was found that the total magnetic moments (TMM) quench in the charged AlLa 12 and BLa 12 clusters with the icosahedral structure 13. Nigam et al studied that the 3 d TM atoms doped the Pd 12 clusters and found that the magnetic characteristics of the Pd 13 clusters were significantly influenced by the dopant 3 d TM atoms 14.…”
Section: Introductionmentioning
confidence: 99%